ANALISIS POLA PENENTUAN LOKASI PEMBANGUNAN PROPERTI MENGGUNAKAN ALGORITMA APRIORI - Alwi Kurniawan; Dicky Apdillah (Smart Education, 2025)
Abstract: This study implements the Apriori algorithm to analyze patterns in property development location selection based on six key attributes: location, soil type, property type, land area, distance to city center, and surrounding facilities. Using a dataset of 100 property records with minimum support of 10%, confidence of 60%, and lift greater than 1.2, the analysis successfully identified significant association rules between land characteristics and suitable property types. The research developed a web-based recommendation system integrating Python for data mining analysis and PHP-mysql for the user interface. Validation results demonstrate that rules such as